Membangun Nasionalisme dan Patriotisme melalui Penciptaan Lagu Anak - Prasetiyo, Ayub; Nugraha, Fahrizal Adi (Resital: Jurnal Seni Pertunjukan, 2022)
ABSTRACT Building Nationalism and Patriotism Through the Creation of Children’s Songs. The tumult of political problems in the past few years has brought the issue of racial discrimination and the rise of horizontal conflicts in society. It can reflect how the state must reformulate policies fostering the four pillars of national life through more communicative media such as music. Music can give us deep experiences which cannot be expressed verbally. Songwriting plays an essential role in teaching and maintaining the values of nationalism and patriotism for children. The method used in this study is a qualitative research method through an experiment in creating songwriting works. In the description, it will use the point of view of autoethnography, which tries to describe the process of this research in narrating the creative efforts of making children's songs which are very subjective from the musical experience of researchers. The results of the study are expected to be able to provide awareness about music and defend the country through appreciation of song lyrics and music itself.ABSTRAK Riuh rendah masalah politik beberapa tahun ke belakang yang membawa isu sara, dan maraknya konflik horizontal di masyarakat dapat menjadi cermin bagaimana negara harus merumuskan ulang kebijakan terkait pembinaan empat pillar kehidupan berbangsa melalui media yang lebih komunikatif seperti musik. Lewat musik kita mendapat pengalaman yang begitu mendalam dan tak bisa diungkapkan secara verbal. Penciptaan lagu menjadi penting perannya guna mengajarkan dan memelihara nilai-nilai nasionalisme dan patriotisme bagi anak-anak. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif melalui sebuah eksprimentasi penciptaan karya cipta lagu. Dalam penjabarannya akan menggunakan sudut pandang autoethnography yang berusaha menguraikan proses penelitian ini dalam menarasikan upaya kreatif pembuatan lagu anak yang sangat subjektif dari musical experience peneliti. Hasil penelitian diharapkan mampu memberikan kesadaran tentang musik dan bela negara melalui penghayatan lirik lagu dan musik itu sendiri.